Workshop on pediatric trauma care: low-cost simulation - Muriel Fernanda de Lima; William Campo Meschial; Hellen Pollyanna Mantelo Cecilio; Jorseli Angela Henriques Coimbra; Maria Gabriela Cordeiro Zago; Vivian Carla de Castro; Roberta Tognollo Borotta Uema; Ieda Harumi Higarashi (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objective: to assess nursing students' and nurses' knowledge, satisfaction and self-confidence after a theoretical workshop on emergency care for traumatized children and clinical simulation. Methods: a quasi-experimental study, carried out with nursing students and nurses residing at a public university in southern Brazil. A workshop on pediatric trauma care was created and a mannequin was created for simulations. A knowledge pre-test and post-test and the Student Satisfaction and Self-Confidence in Learning instrument were applied to measure satisfaction and self-confidence in learning. For analysis, descriptive statistics and the Wilcoxon test were used to compare means before and after intervention. Results: the difference between misses and hits was statistically significant (p<0.005), demonstrating an increase in participants' knowledge after the workshop. Satisfaction and self-confidence were demonstrated in the instrument's high scores. Conclusions: the effectiveness of the workshop in teaching-learning emergency care for pediatric trauma was demonstrated.